Ecological Risk of Heavy Metal Contamination in Sediments of Densely Populated Coastal Area of Sungsang, South Sumatera - Baradelia Sophia Yudhistira; Wike Ayu Eka Putri; Melki (Universitas Muhammadiyah Palembang, 2025)
The coastal waters of Sungsang represent an estuarine area influenced by various anthropogenic activities, including fisheries, agriculture, water transportation, port operations, and domestic waste disposal. Despite the relatively high intensity of these activities, studies specifically assessing the ecological risk of heavy metal contamination in this area remain limited. Therefore, this study aims to provide an initial assessment of the ecological risk associated with Pb and Zn contamination in the coastal waters of Sungsang, South Sumatra. The research was conducted in September 2025, with sediment samples collected from four sampling stations using purposive sampling. Sampling was carried out during a single season; thus, the results represent instantaneous contamination conditions and do not fully reflect annual temporal variations. Heavy metal concentrations were analyzed using Atomic Absorption Spectroscopy (AAS), following SNI No. 06-6992.3-2004 for Pb and SNI No. 06-6992.8-2004 for Zn. The results indicated that the average concentrations of Pb ranged from 14.39 to 19.17 mg/kg, while Zn concentrations ranged from 56.57 to 64.95 mg/kg. Based on sediment quality guidelines, these concentrations are classified as safe for aquatic biota. The geoaccumulation index (I_geo) values indicated that the sediments were unpolluted (I_geo < 0), while the contamination factor (CF) showed low contamination levels (CF < 1). Furthermore, pollution load index (PLI) values of less than one suggests that, overall, the sediments in the Sungsang coastal area have not experienced significant heavy metal pollution.